PENGARUH KONSENTRASI EKSTRAK KASAR KULIT BATANG KUSAMBI (Schleichera oleosa (Lour) Oken) TERHADAP PERTUMBUHAN IN VITRO BAKTERI E. coli - Susilawati, Ni Made; Ramona, Yan; Parwata, I Made Oka Adi (Metamorfosa: Journal of Biological Sciences; Vol 3 No 2 (2016)DO - 10.24843/metamorfosa.2016.v03.i02.p06, 2016)
The main objective of research was to investigate the effectiveness of Schleichera oleosa (Lour) Oken crude extract to inhibit the in vitro growth of E. coli . The crude extract of the plant and the E. coli used in this study were obtained by applying the method of maceration in methanol solution and the method of dilution and spread plate on nutrient agar (NA) medium, respectively. The in vitro bioassay of the extract on E. coli was conducted by applying the method of diffusion on NA medium. The results showed that the crude extract of Schleichera oleosa (Lour) Oken was found to be effective to inhibit the growth of E. coli in the in vitro tests. The diameter of inhibition zone was proportional with the extract concentration exposed to the E. coli .
Keywords: Kesambi tree bark, Escherichia coli, Schleichera oleosa